Young Adult Stroke: The Reality in a Rehabilitation Centre - Henriques, Moisés; Centro de Educação Física da Armada - Centro Hospitalar Lisboa Norte - Hospital de Santa Maria. (2015)
Introduction: This study aims to calculate the percentage of young adults among patients admitted with stroke diagnosis in one Rehabilitation Centre service and study the effect of some parameters on the efficiency of their rehabilitation program in the post-acute phase.Material and Methods: Retrospective, analytical study, drawn up from information contained in the patients admitted in one Rehabilitation Centre service database. Inclusion criteria: hospitalization by cerebrovascular disease diagnosis, namely ischemic or hemorrhagic stroke; first stroke episode and end of hospitalization between January 1, 2007 and December 31, 2012. Exclusion criteria: absence of the event date and readmission. Young adult category was defined for age between 18 and 45 years. It was analyzed the impact of time between event and admission to the rehabilitation centre, type of stroke and laterality on injury inpatient rehabilitation program efficiency in young adults. Z test and t test were used for comparison of proportions and means, respectively.Results: Among patients admitted to the rehabilitation centre because stroke, the annual percentage of young adults ranged from 5% (2010) and 23.3% (2011). The average efficiency of the inpatient rehabilitation program for young adults decreased with increasing number of days that mediated the event and the admission date to the Rehabilitation Centre. The effectiveness of rehabilitation programs in young adults who have suffered an ischemic stroke (versus hemorrhagic) was slightly better, but without statistical significance. Conclusions: The results, while not necessarily representative of the national reality, reveal the relevance of addressing the issue of stroke in young adults with the greatest attention. In young adults, the rehabilitation program efficiency in an inpatient rehabilitation centre decreases with the delay between the stroke event and the Rehabilitation Centre admission.